Bradykinin or acetylcholine as vasodilators to test endothelial venous function in healthy subjects - Rabelo, Eneida R. (2008)
INTRODUCTION: The evaluation of endothelial function has been performed in the arterial bed, but recently evaluation within the venous system has also been explored. Endothelial function studies employ different drugs that act as endothelium-dependent vasodilatory response inductors. OBJECTIVES: The aim of this study is to compare the endothelium-dependent venous vasodilator response mediated by either acetylcholine or bradykinin in healthy volunteers. METHODS AND RESULTS: Changes in vein diameter after phenylephrine-induced venoconstriction were measured to compare venodilation induced by acetylcholine or bradykinin (linear variable differential transformer dorsal hand vein technique). We studied 23 healthy volunteers; 31% were male, and the subject had a mean age of 33 ± 8 years and a mean body mass index of 23 ± 2 kg/m². The maximum endothelium-dependent venodilation was similar for both drugs (p = 0.13), as well as the mean responses for each dose of both drugs (r = 0.96). The maximum responses to acetylcholine and bradykinin also had good agreement. CONCLUSION: There were no differences between acetylcholine and bradykinin as venodilators in this endothelial venous function investigation.